IMPLEMENTING COLLABORATIVE GOVERNANCE: COLLABORATION BETWEEN ACTORS IN ORGANIZING BANYUWANGI FESTIVAL - Bagus Nuari Harmawan; M. Zaenul Muttaqin; Singgih Manggalou (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
The Banyuwangi Festival is the flagship of Banyuwangi tourism on a national level. In addition, the presence of the Banyuwangi Festival also supports the growth of tourist visits to the Banyuwangi area. The success of the Banyuwangi Festival is inseparable from the presence of two significant events, namely the Banyuwangi Ethno Carnival (BEC) and the Gandrung Sewu event. The success of organizing these two significant events cannot be separated from the multi-actor collaboration between the Banyuwangi local government and the private sector to culturalists. This article answers questions about the Collaborative Governance process in the Banyuwangi Festival Program, which consists of the BEC event with the Hybrid Culture theme and Gandrung Sewu with the Traditional theme. This study uses a qualitative comparative method. In Collaborative Governance at the BEC event, the Banyuwangi government cooperates with Dinan Fariz Event Organizer as a private party who provides ideas in terms of conceptual to various detailed elements that support the implementation of a modern carnival. Meanwhile, the Blambangan Arts Council from the Cultural side determines the theme of traditional culture and the party that maintains traditional standards that must be maintained in the implementation of BEC. At the Gandrung Sewu event, the Banyuwangi local government invites cultural cooperation to determine all aspects of culture in the Gandrung Sewu event. Meanwhile, schools and art studios were invited to collaborate to involve their students in the Gandrung Sewu performance. The success of organizing two significant events, namely BEC and Gandrung Sewu, summarized in the Banyuwangi Festival program, cannot be separated from the collaboration of multi-actors who have successfully played their roles by the functions and synergies that have been built between all actors involved.